Southeast Asian Identity Culture: Dynamics, Diversity, and Integration in the Context of Globalization - Abbasovna, Abbasovna (PT. Batari Edu Calya, 2024)
This research explores the dynamics of identity culture in Southeast Asia, focusing on how globalization affects and shapes cultural identities in the region. Using a literature review approach, this study analyzes various literature sources to identify key themes related to cultural diversity, the influence of globalization, and cultural hybridity. Key findings show that Southeast Asia has a rich cultural diversity, with each country in the region displaying unique traditions and customs. However, globalization presents challenges in the form of cultural homogenization, which threatens local uniqueness. Nonetheless, Southeast Asian societies also demonstrate adaptability through cultural hybridity, reflecting the merger of traditional and global elements. This research highlights the importance of preserving local culture while participating in the flow of globalization and proposes policies that support cultural education as well as the preservation of local heritage. These findings offer new insights into how cultural identities in Southeast Asia continue to evolve and transform in response to global change